(untitled) (Proceedings of International Conference on Special Education, 2015)
Young adult Dyslexics still continue to struggle to read texts as the way they see the words are different from normal people. They would take a longer time to read a text passage on screen or printed mediums. This can significantly impede their performances when performing tasks and examinations at higher education institutions or working organisations. Having a tool that can measure their reading competencies is useful as appropriate assistance or support can be given for them to overcome their difficulties. At the moment, readability formulas that measure reading competency are in English, using average words per sentence and average syllables per word. There are differences in constructions of Malay and English words as Malaysian languange tend to have up to five and six more syllables per word when compared to English. This paper will discuss how the existing formulas are analysed and improved to suggest a better instrument that can measure young adults Dyslexics competencies to read Malaysian Language. A range of printed and on screen materials were sampled and studies to match the accuracy of current measurement based on the level of reader competencies, their age groups and a range of reading materials. Preliminary results from this work-in-progress suggest that there are other language parameters that can infuence young adults Dyslexics’ reading competencies such as the used of advanced word and the inclusion of known difficult word for dyslexics in passage. It is expected that the revised formula will increase the accuracy of measuring reading competencies for young adults Dyslexics in Malaysia.